1991
DOI: 10.1177/00220345910700090901
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Thromboxane on Contraction of Canine Mesenteric and Lingual Arteries

Abstract: Thromboxane A2 (TXA2), a potent vasoconstrictor agent, is released from platelets and smooth muscle during inflammation and trauma. TXA2 may cause lingual artery (LA) contraction, leading to lingual paresthesia. The effects of U-46619, a TxA2 mimetic, on isolated rings of canine LA and mesenteric artery (MA) were examined. U-46619 (1 nmol/L to 1 mumol/L) caused a triphasic contraction of LA and MA; a rapid, phasic contraction; a slow, sustained contraction; and, upon washout of U-46619, a maintained contractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…The use of the thromboxane A 2 agonist U46619 to stimulate phasic contractions in this study was necessary to induce consistent and reproducible phasic activity to allow further evaluation of its mechanism. Aside from its powerful smooth muscle tonic contraction response, U46619 has been shown by others to induce phasic activity in the thoracic duct (11), coronary arteries (24), and dog lingual and mesenteric arteries (25). Of interest is the fact that following KCl stimulation the fetal bronchial muscle develops tonic force without phasic contractions suggesting that the mechanism by which U46619 induces rhythmic activity does not depend on the tonic force.…”
Section: Discussionmentioning
confidence: 99%
“…The use of the thromboxane A 2 agonist U46619 to stimulate phasic contractions in this study was necessary to induce consistent and reproducible phasic activity to allow further evaluation of its mechanism. Aside from its powerful smooth muscle tonic contraction response, U46619 has been shown by others to induce phasic activity in the thoracic duct (11), coronary arteries (24), and dog lingual and mesenteric arteries (25). Of interest is the fact that following KCl stimulation the fetal bronchial muscle develops tonic force without phasic contractions suggesting that the mechanism by which U46619 induces rhythmic activity does not depend on the tonic force.…”
Section: Discussionmentioning
confidence: 99%
“…Non‐adjacent vessels were used for each sample to avoid local changes in vascular supply (Greenberg et al. ). Blood samples were taken through IV catheters in one dog from each group, but significant findings were not altered by inclusion of these data.…”
Section: Discussionmentioning
confidence: 99%
“…Greenberg et al (4) reported that the lingual artery in dogs has a very different response to the stimulation of calcium influx than the mesenteric artery or other vessels. Moreover, Tsukada and Chiba (13) showed a depressed vasoconstrictive effect of norepinephrine on the lingual artery that was not reproducible in the mesenteric vessels when they were submitted to changes in temperature.…”
Section: Microcirculation Studies In Dogsmentioning
confidence: 99%